Association Between Serum Cotinine Level and Serological Markers of Epstein–Barr Virus in Healthy Subjects in South China Where Nasopharyngeal Carcinoma Is Endemic - Yang, Qian-Yi; He, Yong-Qiao; Xue, Wen-Qiong; Zhou, Ting; Liao, Ying; Zheng, Mei-Qi; Jia, Yi-Jing; Yuan, Lei-Lei; Jia, Wei-Hua (Frontiers in Oncology, 2019)
Introduction Self-reported smoking has been associated with higher seropositivity for the IgA response to Epstein-Barr virus (EBV) viral capsid antigen (VCA-IgA) and transcription activator protein (Zta) in healthy men in southern China where nasopharyngeal carcinoma (NPC) is endemic. Results on the association of biochemically verified smoking status with EBV reactivation are scarce. We aimed to investigate the relations of serum cotinine level with serological markers of EBV in healthy women, in addition to men. Methods We collected information on demographic, lifestyle, environmental factors, and EBV serological markers in a cross-sectional study on 2275 healthy subjects who were recruited from physical examination centers in Guangdong Province, China. In present analysis, 901 subjects’ serum cotinine levels have been measured by ELISA. Odds ratios (seropositivity of four EBV serological markers versus seronegativity) for categorical serum cotinine levels were calculated by unconditional logistic regression with a group-specific confidence interval (CI). Results In women, compared with lower serum cotinine level (0-0.71 ng/ml), higher cotinine level (>0.71-1.20 ng/ml; >1.20-228.40 ng/ml) was associated but non-significantly with higher seropositivity for EBV VCA-IgA (age- and education-adjusted OR=1.18, 95% CIs=0.84-1.64, 1.06, 0.75-1.50). These associations remained but still non-significant after adjusting for 5-year age group, education, family history of cancer, consumption of tea, Chinese herbal tea, and salted fish at childhood, and exposure to occupational dust, chemical, fume and radiation (multivariable adjusted OR=1.21, 95% CIs=0.85-1.71, 1.09, 0.76-1.55). In men, compared with lower serum cotinine level (0-2.15 ng/ml), higher cotinine level (>2.15-103.6 ng/ml; >103.6-419.4 ng/ml) was significantly associated with higher seropositivity for EBV VCA-IgA and Zta-IgA (age- and education-adjusted OR=2.16, 95% CIs=1.37-3.41, 1.79, 1.11-2.90; 1.98, 1.17-3.34, 1.95, 1.14-3.34). The association remained significant after adjusting for potential confounders for Zta-IgA (OR=2.32, 95% CI=1.37-3.93 for >2.15-103.6, and 2.50, 1.43-4.38 for >103.6-419.4 ng/ml), but not for VCA-IgA (2.06, 1.29-3.27, and 1.61, 0.96-2.71). Conclusions Higher serum cotinine level is associated with higher seropositivity for EBV serological markers in healthy men in southern China. Such positive association was also observed in women but became non-significant. If confirmed to be causal, this finding has important implications for tobacco control and prevention of EBV-related disease, particularly for NPC.